Primary Hepatic Lymphoma in a 32-year-old Male - Nurria Betty Indriyaningrum; Syifa Mustika (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2017)
A 32-year-old male came with right upper abdominal pain with a mass increasing in size since the last 6 months, with no other typical symptoms. The physical findings revealed right upper abdominal mass, rubbery consistence, irregular surface, rounded edge, unclear border, immobile, without any tenderness. Other physical examination revealed normal findings, without any lymphadenopathy at another site. The laboratory findings revealed non-reactive hepatitis B and C markers, normal AFP, slightly increased LDH. Plain chest X-ray showed elevated right hemidiaphragm, and a large mass sized ± 14.18 x 8.56 x 12.56 cm compressing the liver. We’ve done biopsy with ultrasound guiding on the mass, and the histological examination revealed that it was lymphoma with negative CD20. The diagnosis was established as primary hepatic lymphoma and the patient was then given chemotherapy.